Translating Heimat in Multilingual Dortmund - Kristin Dickinson (Studies in 20th & 21st Century Literature, 2024)
Named for the people of 132 different nationalities photojournalist Peyman Azhari encountered in northern Dortmund over the course of a year, the photo collection Heimat 132 (2014) stands as testament to the many ethnicities, religions, and languages this neighborhood is home to. In my paper, I read Azhari’s photographs as sites of translation capable of reclaiming a critical understanding of Heimat (home or homeland) that is fundamentally multilingual. I do so by first exploring the link between racially and ethnically exclusionary definitions of Heimat and the all-too-common assertion that Heimat is an untranslatable word. Each approach, I argue, rests on assumptions of origins and originality, which understand Heimat as a pre-given way of life that can be threatened and is thus in need of preserving. Through its linguistic and visual engagement with this term, I argue, Azhari presents Heimat rather as a radically open and collaborative process of belonging in the making. Starting with a series of portraits and interviews in the second half of the collection, I consider Azhari’s decision to render multilingual conversations with residents into seemingly monolingual German narratives that are nevertheless punctuated by a series of translations of the word Heimat. By repeatedly rendering this term both out of, and then back into German, the collection allows Heimat to brush up against a range of words in other languages, including home (casa), motherland (matribomi), fatherland (atdhe), and ancestral homeland (guxiang), among others. If, through the act of translation, Azhari asks readers to approach the concept of Heimat relationally rather than as an inherently German term, translation then also punctuates these otherwise monolingual narratives, thereby breaking the link between Heimat and nativity at the core of right-wing appropriations of the word. Azhari suggests, on the contrary, that multilinguality and the non-local play an active role in the production of Heimat, and that translation—and more specifically translational difference—is central to the concept of belonging it has the power to generate. By repeatedly foregrounding their own non-transparency, the portraits and streetscapes of Heimat 132 similarly present themselves as sites of translation, rather than as universally accessible documents. Together with the collection’s recurrent translations of the word Heimat, they capture sites of linguistic and cultural contact in the aftermath of migration that reveal this neighborhood, but more importantly German culture itself, to be a dynamic site of translation. As viewers—from either within or outside of Dortmund—we are central to this process of translation, which can only come to fruition through our viewing practice and our critical engagement with the photographs.
Keywords: Heimat; Translation; Multilingualism; Dortmund; Peyman Azhari; Photography